Phase I Clinical Trial of the Chimeric Anti-Mesothelin Monoclonal Antibody MORAb-009 in Patients with Mesothelin-Expressing Cancers - Hassan, Raffit; Cohen, Steven J.; Phillips, Martin; Pastan, Ira; Sharon, Elad; Kelly, Ronan J.; Schweizer, Charles; Weil, Susan; Laheru, Daniel (Clinical cancer research, 2010)
Purpose: MORAb-009 is a chimeric monoclonal antibody that targets mesothelin, a tumor differentiation antigen overexpressed in pancreatic cancer, ovarian cancer, mesothelioma, and other malignancies. We conducted a phase I clinical trial of MORAb-009 in patients with advanced mesothelin-expressing cancers to determine its safety, dose-limiting toxicity (DLT), and maximum tolerated dose (MTD). Methods: Cohorts consisting of 3 to 6 subjects each received MORAb-009 intravenously on days 1, 8, 15, and 22 at progressively increasing doses ranging from 12.5 to 400 mg/m2. Disease evaluation with computed tomography occurred on day 35. Subjects with responding or stable disease could receive additional cycles of MORAb-009. Results: A total of 24 subjects were treated including 13 mesothelioma, 7 pancreatic cancer, and 4 ovarian cancer patients. The median number of MORAb-009 infusions was 4 (range 1–24 infusions). At the 400 mg/m2 dose level, 2 subjects experienced DLT (grade 4 transaminitis and a grade 3 serum sickness). Thus, although there were other contributing causes of these adverse events, 200 mg/m2 was considered the MTD. Other adverse events at least possibly related to MORAb-009 included 7 drug hypersensitivity events (all grade 1 or 2) and a thromboembolic event (grade 4). Eleven subjects had stable disease. There was a dose-dependent increase in serum MORAb-009 concentration. Conclusion: MORAb-009 is well tolerated and the MTD when administered weekly is conservatively set at 200 mg/m2. In this group of previously treated patients, 11 subjects had stable disease. Phase II studies of MORAb-009 in different mesothelin-expressing cancers are ongoing.